RELATION BETWEEN ANOMALOUS EATING BEHAVIORS AND OTHER HEALTH BEHAVIORS IN CHILDREN 11-14 YEARS OLD - Guirado Martínez, Mª Carmen; Ballester Arnal, Rafael (Anales de Psicología / Annals of Psychology, 2005)
The aim of this work is to analyze the existing relation among anomalous eating behaviors and among these eating behaviours and other behaviors, such as sleep habits, school absenteeism, consumption of alcohol and other drugs, poor self-esteem, emotional welfare, control of impulses, physical exercise and sexual behaviour. We have administered to a sample of 819 adolescents 11-14 years old, the Questionnaire of Information, Attitudes and Behaviors related to Health (CIACS II). The results evidence important relations among specific anomalous eating behaviors, as avoidance of fat food, weight control, to do exercise in order to burning calories and vomiting after an abundant meal. Also, we have found significant correlation among specific problematic eating behaviors and other behaviors as having difficulties to get to sleep, school absenteeism, to feel sad when they believe to have injured the feelings of the others, difficulty to control impulses, consumption of alcohol or the desire to change many things of oneself.